Happiness Index of Nepal; Rhetoric and Reality: A Sustainable Development Prospective (Rural Development Journal, 2026)
This article aims to examine the scenario of happiness index of Nepal on sustainable development perspective. Happiness Index is a tool of measuring the psychological well-being of an individual and community. The measurement of subjective emotion is quite complex. It has multidisciplinary domains. The research is based on secondary sources of information. The conclusion is drawn by analyzing both qualitative and quantitative data. Nepalese happiness index is more fluctuated. Despite the socio-economic disparities of the society, the happiness index of the country is remarkable. Nepal is ranked in 92th out of 147 countries in happiness index whereas it is ranked in 85th out of 167 countries in the world in sustainable development. Sustainable development is comprehensive approach towards the progress of nation that provide equal significant to the subjective well-being. The article examined that the sustainable development goal could not cover the entire issue of happiness domain. Social support, community support, good governance, job satisfaction, generosity and socio-cultural engagement are some of the missing indicators of sustainable development on happiness index.